Nonviral Transfection With Brachyury Reprograms Human Intervertebral Disc Cells to a Pro‐Anabolic Anti‐Catabolic/Inflammatory Phenotype: A Proof of Concept Study. Issue 11 (29th July 2019) - Tang, Shirley; Richards, Justin; Khan, Safdar; Hoyland, Judith; Gallego‐Perez, Daniel; Higuita‐Castro, Natalia; Walter, Benjamin; Purmessur, Devina
ABSTRACT: Intervertebral disc (IVD) degeneration is a major contributor to chronic low back pain and is characterized by decreases in cellularity and proteoglycan synthesis, upregulation of matrix degradation, and increases in pro‐inflammatory factors with neurovascular invasion. Current treatments fail to target the underlying pathology or promote tissue repair and approaches such as viral transfection raise safety concerns due to mutagenesis and unwarranted immune responses. To avoid such concerns, nonviral transfection is a viable method of gene delivery into the host cell while bypassing the caveats of viral delivery. Brachyury is expressed in the developing notochord and is associated with an immature healthy nucleus pulposus (NP). We hypothesize that Brachyury can reprogram degenerate NP cells to a healthy pro‐anabolic phenotype with increased proteoglycan content and decreased expression of catabolic, inflammatory, and neurovascular markers. NP cells obtained from human autopsy and surgical tissues were transfected with plasmids encoding for Brachyury or an empty vector control via bulk electroporation. Post transfection, cells were seeded in three‐dimensional agarose constructs cultured over 4 weeks and analyzed for viability, gene expression, and proteoglycan. Results demonstrated successful transfection of both autopsy and surgical NP cells. We observed long‐term Brachyury expression, significant increased expression of NP phenotypic markers FOXF1, KRT19, and chondrogenic marker SOX9 with decreases in inflammatory cytokines IL1‐β/IL6, NGF, and MMPs and significant increases in glycosaminoglycan accumulation. These results highlight nonviral transfection with developmental transcription factors, such as Brachyury, as a promising method to reprogram degenerate human disc cells toward a healthy NP phenotype. Clinical significance: This project proposes a novel translational approach for the treatment of intervertebral disc degeneration via direct reprogramming of diseased human patient‐derived IVD cells to a healthy phenotype. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:2389–2400, 2019